Long term impacts of class size in compulsory school - Edwin Leuven; Sturla A. Løkken (Statistics Norway, Research Department, 2017)
How does class size in compulsory school affect peoples' long run education and earnings? We use maximum class size rules and Norwegian administrative registries allowing us to observe outcomes up to age 48. We do not find any indication of beneficial effects of class size reduction in compulsory school. For a 1 person reduction in class size we can rule out effects on income as small as 0.087 percent in primary school and 0.12 percent in middle school. Population differences in parental background, school size or competitive pressure do not appear to reconcile our findings with previous studies.
Keywords: I21; I28; J24; C30; 330; Class size; Schooling; Earnings; Regression Discontinuity